High Prevalence of Antiphospholipid Antibodies in Children with Non-Transfusion Dependent Thalassemia and Possible Correlations with Microparticles - Jitlada Chinsuwan; Phatchanat Klaihmon; Praguywan Kadegasem; Ampaiwan Chuansumrit; Anucha Soisamrong; Kovit Pattanapanyasat; Pakawan Wongwerawattanakoon; Nongnuch Sirachainan (Mediterranean Journal of Hematology and Infectious Diseases)
Antiphospholipid antibodies (APAs) are developed antibodies to the phospholipid surfaces or to the proteins binding to phospholipids. Increased PS-expressed red blood cells (RBC) may be a risk factor in APAs development. There were only a few studies reported on APAs in thalassemia, and their associations to PS-expressing microparticles (MPs), remain unknown. The presence of antiphospholipid antibodies (APAs) in pediatric thalassemia patients and their associations with phosphatidylserine (PS)- expressing microparticles (MPs), a previously unexplored relationship, were the aims of this report. We identified that positive APA rates were highest in non-transfusion-dependent thalassemia (NTDT) subjects, followed by transfusion-dependent thalassemia (TDT) subjects and controls (29.5%, 18.2% and 17.9%, respectively).  Subgroup analysis demonstrated that positive anti- ?2 glycoprotein I (a?2-GPI)- IgG rates in NTDT subjects were significantly greater than in controls and that the percentage of MPs was also significantly elevated in thalassemia subjects. More specifically, there were significant correlations found between a?2GPI-IgG and anticardiolipin (aCL)-IgM APAs, and MPs.